Manejo e conservação da agrobiodiversidade no assentamento rural Olga Benário no estado de Sergipe - Almeida, Ana Cristina Oliveira de (Universidade Federal de São Carlos, 2014)
The paradigm of the rural development through globalization of agricultural markets has affected the diversity of natural resources and, on the condition of the rural settlements, this situation of loss becomes worse seen the heterogeneity of subjects and the existing structural difficulties. This work aims to analyze through native seeds the local conservation of agricultural biodiversity and the management carried out by the settled farmers in Olga Benário Settlement Project located in Sergipe. Two systems of different treatments were identified and, through indicators of low, medium and high levels of agroecosystem analysis was conducted. In large lots, crops which showed more diversity were the fava bean, maize, bean, cowpeas, cassava, bananas, yam and sweet potato. Highlighting the cultures of cassava which showed that seed exchange network established. The absence of an irrigation system and sufficient supply of fertilizer for the production have been identified as limiting factors for further integration of production. Farmers were presented as potential guardians of seeds, as noted in the analysis of the exchange of cassava manivas network which was more significant in relation to other cultures. The construction of Agroecology is seen as the way for the local knowledge reframing agriculture are transmitted, starting with the rescue of native seeds.
Management and conservation in rural agrobiodiversity Olga Benário settlement in Sergipe
Keywords: Desenvolvimento rural; Agrobiodiversidade; Manejo; CIENCIAS AGRARIAS